Changes to Deliberation Norms in the 1945 Constitution of the Republic of Indonesia - Shalahuddin (Journal of Legal and Cultural Analytics, 2023)
The purpose of this study is to find out the meaning and existence of deliberation as a system in government as stated in article 18 of the 1945 Constitution of the Republic of Indonesia (UUD NRI) before the amendment. This research was conducted using normative juridical research methods, with a historical approach and a conceptual approach. With the results of the study explaining that Deliberation is a religious order as explained in 3 (three) verses in the Al-Qur'an which contains orders for deliberation, namely: First, Q.S. Al-Baqoroh/2: 233. Second, Q.S. Ali Imron / 3: 159. Third, Q.S. asy - Syûro/42: 38. As for its position in Indonesia in the perspective of a rule of law, the order for deliberation has been listed as the basis of the State, namely in Pancasila, namely the fourth precept which reads "Populist Led by Wisdom of Wisdom in Deliberation/Representation" and in the stem The body of the 1945 NRI Constitution was also included in Article 18 before the amendment.